2019
DOI: 10.3233/wor-192886
|View full text |Cite
|
Sign up to set email alerts
|

Levels of physical activity and associated factors between military policemen and firemen

Abstract: BACKGROUND: Military Policemen and Firemen are professionals often involved in life-risking activities as well as duties demanding endurance and muscular strength. Nevertheless, their working conditions are rarely satisfactory. OBJECTIVE: To compare levels of physical activity and social, demographic and occupational factors between military policemen and firemen; factors that may impact their ability to efficiently and effectively accomplish their jobs. METHODS: This cross-sectional study was performed in Bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The most prevalent CVD risk factors among firefighters include obesity ranging between 14% and 60% [16][17][18][19], hypertension between 10% and 44% [17,[20][21][22][23], cigarette smoking ranging between 11% and 39% [24][25][26][27][28][29][30], dyslipidemia between 20% and 56.5% [17,27,[31][32][33], and physical inactivity between 14.7% and 70% [10,[34][35][36][37][38][39]. These risk factors have been reported to consistently lower cardiorespiratory fitness in firefighters [30,35,[40][41][42], primarily due to reducing vascular elasticity, reducing preload, and increasing afterload, and subsequently, reducing stroke volume and oxygen transportation to working muscles [43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…The most prevalent CVD risk factors among firefighters include obesity ranging between 14% and 60% [16][17][18][19], hypertension between 10% and 44% [17,[20][21][22][23], cigarette smoking ranging between 11% and 39% [24][25][26][27][28][29][30], dyslipidemia between 20% and 56.5% [17,27,[31][32][33], and physical inactivity between 14.7% and 70% [10,[34][35][36][37][38][39]. These risk factors have been reported to consistently lower cardiorespiratory fitness in firefighters [30,35,[40][41][42], primarily due to reducing vascular elasticity, reducing preload, and increasing afterload, and subsequently, reducing stroke volume and oxygen transportation to working muscles [43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…6,22 However, many firefighters are not participating in physical activity regularly in their leisure time, which is a cause for concern. 11,23,24…”
Section: Introductionmentioning
confidence: 99%
“…6,22 However, many firefighters are not participating in physical activity regularly in their leisure time, which is a cause for concern. 11,23,24 Currently, in the City of Cape Town Fire and Rescue Service (CoCTFRS), research has indicated that a relatively small percentage of firefighters are physically inactive. 25 However, these statistics include occupational activity minutes, not leisure time activity or recreational activity only.…”
Section: Introductionmentioning
confidence: 99%